STRATEGI PEMBANGUNAN PENDIDIKAN DAERAH - Elvis Ardi (Universitas Riau, 2016)
Strategy Education Local Development. This study aims to investigate the implementationof the education development strategy Rokan Hilir district governments through the analysis ofkey performance indicators of educational development. The method used in this study lead to theuse of qualitative research methods. Qualitative research can be defined as research that producesdescriptive data on the spoken word and tertulisdan behavior that can be observed from the peoplestudied. The results showed in order to realize the vision and mission, then in RPJMD Rokan Hilir,formulated a strategy which is activity, mechanisms or systems to anticipate and predict the overallachievement of the goals ahead through a rational approach. The strategy in the field of educationdevelopment in Rokan Hilir RPJMD is strengthening education, fostering religion, and morality forsociety in order menanggulani negative impact of globalization.